Percutaneous hallux valgus surgery: strengths and weakness in our clinical experience - Pichierri, P.; Sicchiero, P.; Fioruzzi, A.; Maniscalco, P. (Acta Biomedica Atenei Parmensis, 2014)
Background and aim of the work: The Reverdin-Isham percutaneous osteotomy is indicated in the treatment of mild to moderate hallux valgus deformity. The aim of the work is the evaluation of the technique itself as a possible future landmark in the hallux valgus treatment. Methods: Between January 2010 and January 2011 we have performed 138 percutaneous osteotomies. The patients were assessed with a clinical and radiological control after a median five months follow up. The score proposed by the American Orthopaedic Foot and Ankle Society was used for the clinical evaluation. Results: The average score has improved from a preoperative median of 45 points to a postoperative median of 91 points. The technique has been largely accepted by the patients because of the speed of the procedure itself, the minimal invasiveness, the short pain and the immediate functional recovery. Conclusions: The results we have obtained with the Reverdin-Isham procedure have confirmed that this technique is a valid alternative to other percutaneous techniques and open surgical procedures. However the technique is not simple, it needs the strict indications observance and it needs a steep learning curve, those are features that impose further future studies. (www.actabiomedica.it)